2000
DOI: 10.1097/00003246-200007000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous oxygen and CO2 as early warning of tissue hypoxia and hemodynamic shock in critically ill emergency patients

Abstract: PtcO2 and PtcCO2 monitoring continuously evaluate tissue perfusion and serve as early warning in critically injured patients during resuscitation immediately after hospital admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 12 publications
3
66
1
1
Order By: Relevance
“…Preliminary reports regarding regional CO 2 measurement in sensible microvascular beds, as manifestation of hypoperfusion, are promising [71][72][73]. Measurement of oxygen tension or saturation in certain tissues has permitted the identification of occult hypoperfusion in animal studies and in some limited clinical experiences published [71,[74][75][76][77][78].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Preliminary reports regarding regional CO 2 measurement in sensible microvascular beds, as manifestation of hypoperfusion, are promising [71][72][73]. Measurement of oxygen tension or saturation in certain tissues has permitted the identification of occult hypoperfusion in animal studies and in some limited clinical experiences published [71,[74][75][76][77][78].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…These authors concluded that PtcO 2 and PtcCO 2 monitoring continuously evaluated tissue perfusion and served as an early warning in critically injured patients during resuscitation immediately after hospital admission. 48 Transfusion Alternatives in Transfusion Medicine VOLUME 6 NUMBER 4 MARCH 2005…”
Section: Near-infrared Spectroscopymentioning
confidence: 99%
“…The measurement of transcutaneous P CO 2 (P tcCO 2 ) has been examined in critically ill [14][15][16] or ventilated adults 17,18 and newborns, 19 as well as during bronchoscopy 20 or interhospital ground transport. The aim of our study was to compare P tcCO 2 with P capCO 2 in hypercapnic subjects during the night.…”
Section: Introductionmentioning
confidence: 99%